Evolution of Teamwork Quality Instruments in Agile Software Development: A Systematic Literature Review - Santos, Ramon Nóbrega dos; Cunha, Felipe Oliveira Miranda; Rique, Thiago Pereira; Perkusich, Mirko; Sousa Neto, Ademar França de; Albuquerque, Danyllo Wagner; Almeida, Hyggo; Perkusich, Angelo (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2023)
[Context] Multiple models (or instruments) for measuring Teamwork Quality (TWQ) and Teamwork Effectiveness (TWE) for Agile Software Development (ASD) have been created. However, such models have different constructs and measures, with a limited understanding of how they are related and have evolved. [Goal] Our goal is to identify all ASD instruments to gain insights into the evolution of specific instruments for ASD. [Method] We performed a systematic review methodology using a search string and a forward snowballing approach to identify the specific instruments that assess TWQ and TWE. Later, we conducted a frequency analysis of the factors measured by these ASD instruments. [Results] We provided a comprehensive view of the evolution of teamwork instruments in ASD and classified them into Generic teamwork instruments and Agile-based teamwork instruments. We found that these instruments have evolved with the more specialized factors specific to the agile context. In addition, they have semantically similar factors with different factor names, pointing to the need for terminology standardization. [Conclusion] A conceptual framework integrating the instrument factors within the agile context is needed. We advocate further studies on this topic, aiming to develop a unified taxonomy to be taken as a reference for constructing new teamwork instruments.